Multi-drug resistant Clostridioides difficile isolate ST81 is prominent in hematological patients in a teaching hospital in China - Zhao, Qi; Bian, YaoQian; Wei, XinJun; Xiao, Shuzhen; Xu, Zizhen; Li, Hui; Li, Qingtian; Wei, Beiwen; Huang, Jiewen; Song, Zhen; Zhao, Yanan (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionClostridioides difficile Infection (CDI) is more prevalent in people with hematologic diseases. However, epidemiological characteristics are poorly understood.MethodsFrom July 2016 to November 2021, we studied the epidemiology of CDI in patients with hematological diseases at a tertiary teaching hospital in Shanghai, China.ResultsIn hematological patients, the prevalence of CDI was 21.6%, with 89.8% hospital-acquired infections. C. difficile ST81, which is a multidrug-resistant strain carrying only the toxin B, is the most common strain (38.1%), followed by ST3 (16.7%) and ST2 (9.5%). Clindamycin and moxifloxacin resistance rates of all C. difficile species were 64.3% and 31%, respectively, and no isolate was resistant to vancomycin, linezolid, metronidazole, teicoplanin, or daptomycin. DiscussionThis study provides a comprehensive characterization of CDI in hematological patients, highlighting the urgent need for enhanced surveillance and preventive strategies against this emerging nosocomial threat.